2010
DOI: 10.1111/j.1365-2559.2010.03552.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nasal mucosa as a new target for leptin action

Abstract: Leptin receptors and their biological ligand leptin are expressed in the nasal mucosa, suggesting a possible role in upper airway immunology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Similar to the native protein, the LepNP85 conjugate at least in part used a saturable pathway for the distribution to the serum that was inhibited by co-administration of the free hormone. It is known that leptin receptors are expressed in human nasal mucosa [6770] and serum levels of leptin were shown to positively correlate with that of nasal leptin in human [67]. Based on this, we believe that both the membrane binding of the PPO block and the receptor/transporter binding of the leptin might be responsible for the serum penetration of this conjugate after intranasal delivery.…”
Section: Discussionmentioning
confidence: 62%
“…Similar to the native protein, the LepNP85 conjugate at least in part used a saturable pathway for the distribution to the serum that was inhibited by co-administration of the free hormone. It is known that leptin receptors are expressed in human nasal mucosa [6770] and serum levels of leptin were shown to positively correlate with that of nasal leptin in human [67]. Based on this, we believe that both the membrane binding of the PPO block and the receptor/transporter binding of the leptin might be responsible for the serum penetration of this conjugate after intranasal delivery.…”
Section: Discussionmentioning
confidence: 62%
“…The Meta‐analysis of mean serum leptin levels of patients with CRS compared to healthy controls was completed on 2 eligible articles (Table 1). 10,11 Additionally, a separate Meta‐analysis was performed on 4 eligible studies that reported ORs on the prevalence of CRS based on the presence of overweight/obesity.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review on this topic found that the majority of the fifteen studies assessing the mean serum leptin levels of asthma patients with obesity reported elevated levels compared to the control subjects 9 . Similarly, previous research has found that patients with nasal polyposis have higher levels of serum leptin compared to healthy control subjects 10,11 …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In the nasal tract, upon injury, undifferentiated basal cells migrate from adjacent epithelium, spread over the denuded basement membrane, and proliferate in injured regions [7]. Despite leptin playing different roles in the olfactory mucosa cells [8], in the human nasal epithelium, its role is still largely unexplored.…”
Section: Introductionmentioning
confidence: 99%